Living in an estuary: Commerson´s dolphin (Cephalorhynchus commersonii (Lacépède, 1804)), habitat use and behavioural pattern - Loizaga de Castro, Rocio (2013)
Commerson?s dolphins, Cephalorhynchus commersonii, suffer bycatch in fisheries and are target of dolphin-watching activities along Patagonia. Here we described dolphins? habitat use and behavioural pattern at the estuary of Santa Cruz River. Behavioural observations were made from vantage points using a spotting scope. Boat surveys were conducted randomly from Puerto Santa Cruz to the mouth of the river to analyze the habitat use. The survey area was divided into 1 km2 cells and characterized with depth and benthic slope. The described behaviours for the Commerson?s dolphin were: travelling, slow travelling, milling, resting, socializing, stationary swimming and diving. A new behavioural context was assigned to diving, a behaviour that showed a high frequency during downing tide, suggesting a benthic foraging strategy. Additionally, we found a strong influence of the tide on Commerson´s dolphin behaviour. Habitat use models indicated that dolphins prefer shallow water inside the estuary. The knowledge of the behavioural patterns and the habitat use of these endemic species, in this unexplored area, provide tools for management and conservation purposes.